Formulation Science and Technology. - Tadros, Tharwat F., 1937- (De Gruyter, 2018)
Volume 4 of Formulation Science and Technology is a survey of the applications of formulations in a variety of fields, based on the theories presented in Volumes 1 and 2. It offers in-depth explanations and a wealth of real-world examples for research scientists, universities, and industry practitioners in the fields of Agrochemicals, Paints and Coatings and Food Colloids.